Design and implementation of potentiometer-based nonlinear transducer emulator - Khan, Sheroz; Omar, Jamaluddin; Hasan, Sk Khairul; Md Ralib, Aliza Aini Binti; Ya, Ma Li; Arshad, Atika; Hussin, Hanum Syahida; Mohd Nor, Norhanis Aida; Alam, A. H. M. Zahirul; Islam, Md. Rafiqul (IIUM Press, 2011)
This work attempts to design and implement in hardware a transducer with a nonlinear response using potentiometer. Potentiometer is regarded as a linear transducer, while a the response of a nonlinear transducer can be treated as a concatenation of linear segments made out of the response curve of an actual nonlinear transducer at the points of inflections being exhibited by the nonlinear curve. Each straight line segment is characterized by its slope and a constant, called the y-intercept, which is ultimately realized by a corresponding electronic circuit. The complete circuit diagram is made of three stages: (i) the input stage for range selection, (ii) a digital logic to make appropriate selection, (iii) a conditioning circuit for realizing a given straight-line segment identified by its relevant slope and reference voltage. The simulation of the circuit is carried using MULTISIM, and the designed circuit is afterward tested to verify that variations of the input voltage give us an output voltage very close to the response pattern envisaged in the analytical stage of the design. The utility of this work lies in its applications in emulating purpose built transducers that could be used to nicely emulate a transducer in a real world system that is to be controlled by a programmable digital system.